Cerebrospinal Fluid Drainage During Endovascular Aortic Aneurysm Repair: A Systematic Review of the Literature and Treatment Recommendations. (April 2020) - Malloy, Patrick C.; Raghavan, Alankrita; Elder, Theresa; Wright, James; Wright, Christina Huang; Burant, Christopher; Sajatovic, Martha; Hoffer, Alan
Introduction: Spinal cord injury (SCI) is a known complication of aortic aneurysm repair. Previous reports indicate that cerebrospinal fluid drainage (CSFD) may reduce incidence of SCI during open aortic aneurysm repair but its utility in endovascular repair remains poorly understood. We performed a systematic review of the literature to examine the protocols and outcomes of CSFD in patients undergoing endovascular aortic aneurysm repair. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines were utilized to conduct a systematic literature review. PubMed, Scopus, Ovid, Cochrane, and EMBASE were queried for articles published since 2016 using search terms "(cerebrospinal fluid diversion OR CSF diversion OR lumbar drain OR subarachnoid drain OR spinal) AND (aortic aneurysm AND thoracic AND endovascular OR TEVAR)." Ninety-two articles were identified and screened by 2 independent reviewers, and 23 studies met criteria for full-text review after initial screening. Results: A total of 8 studies met full inclusion criteria for final analysis. Six studies reported incidence of SCI in patients with CSFD and 2 compared SCI incidence between patients with and without CSFD. Protocols for drainage most commonly included draining to a target pressure intra- and postoperatively, between 8 and 12 mm Hg. Incidence of SCI ranged from 0% to 17% in patients with CSFD, and from 0% to 50% in those without CSFD. Rates of CSFD-related complications ranged from <1% to 28%. Conclusion: There may be a protective benefit of CSFD in preventing SCI, but there remains significant variation in drain placement protocols. Significant potential bias exists in the reviewed data. Higher quality studies on the role of CSFD in endovascular aortic aneurysm repair are needed.